Identificación de formaldehído en champúes cosméticos expendidos en el mercado La Hermelinda de Trujillo, marzo 2015 - Carranza Barreto, Karen (2015)
This research aimed to identify formaldehyde in cosmetic shampoos expended in the Hermelinda market Trujillo in March 2015.Trabajamos to the method of Ho Georghiou and whose mechanism is the union of two molecules of chromotropic acid when it reacts with the formaldehyde, in a strongly acidic medium (H2SO4) and under heating in a water bath through a methylene bridge. The result of chromotropic acid and formaldehyde in the presence of a red-violet color is observed. Ballerina®, Amens®, Johnson's®, EGO®, Savital®, Pantene®, Konzil®, Petit Post Pon®: samples of the following brands of shampoos were studied. By analysis it was found that 75% of shampoo brands: Ballerina®, Amens®, Johnson's®, EGO®, Savital® and Konzil®, have formaldehyde in its formulation; and 25% for the Pantene® and Petit Post Pon® brands do not show formaldehyde in its formulation